SECURITY RISKS OF LANDMINES AND EXPLOSIVE ORDNANCE IN BOSNIA AND HERZEGOVINA (Security Dialogues, 2026)
Various security risks have persisted in Bosnia and Herzegovina even after the cessation of the armed conflict. Mines and explosive remnants of war continue to constitute a significant source of security threats to both the population and the environment. The loss of human lives, the infliction of severe bodily injuries, the inability to utilize agricultural land, the deterioration of soil quality, and the degradation of groundwater represent some of the adverse consequences of the presence of mines and explosive ordnance in Bosnia and Herzegovina. The absence of comprehensive documentation regarding mines, coupled with persistent financial constraints, further complicates and delays the process of land decontamination.References•     Akhgari F., Fattahi H., Oskoei Y. M. (2015) Recent advances in nanomaterial-based sensors for detection of trace nitroaromatic explosives. Sensors and Actuators B Chemical Vol. 221, 867–878.•     Berhe A. A. (2000) Landmines and land degradation: A Regional Political Ecology Perspective On The Impacts Of Landmines On Environment And Development In The Developing World. Masters Paper. Michigan State University.•     BHMAC (2024) Plan deminiranja u BiH za 2024. godinu. chrome-extension: //efaidnbmnnnibpcajpcglclefindmkaj/https://www.bhmac.org/wp-content/uploads/2024/06/Plan-deminiranja-u-BiH-za-2024-Prijedlog.pdf (приступљено 01.09.2025.)•     BHMAC (2025) Minska situacija, https://www.bhmac.org/trenutna-minskasituacija-plan-izvjestaj/ (приступљено 03.09.2025.)•     BHMAC (2017), Стратегија Противминског Дјеловања Босне и Херцеговине 2018-2025, chrome-extension://efaidnbmnnnibpcajpcglclefindmkaj/https://www.bhmac.org/wp-content/uploads/2024/06/Strategija-Protivminskog-djelovanja-uBiH-2018-2025-1.pdf (приступљено 10.08.2025.)•     Friends of the Earth Flanders & Brussels. (2007) Landmines in Bosnia and Herzegovina, chrome extension://efaidnbmnnnibpcajpcglclefindmkaj/http://atlas.geog.pmf.hr/~nbuzjak/mine/BHMAC_en.pdf (приступљено 27.08.2025.)•     GICHD (2021) Guide to Explosive Ordnance Pollution of the Environment.chromeextension://efaidnbmnnnibpcajpcglclefindmkaj/https://www.gichd.org/fileadmin/uploads/gichd/Publications/EO_Pollution_of_the_Environment_v17_web_01.pdf (приступљено 12.08.2025.)•     GICHD, UNDP (2022) Rezultati protivminskog djelovanja u Bosni i Hercegovini ukontekstu održivog razvoja”. chrome-extension://efaidnbmnnnibpcajpcglclefindmkaj/https: //www.gichd.org/fileadmin/uploads/gichd/Publications/Rezultati_protivminskog_djelovanja_u_Bosni_i_Hercegovini_u_kontekstu_odrzivog_razvoja.pdf.•     Khan M. I., Lee J., Park J. (2012) Microbial Degradation and Toxicity of Hexahydro1,3,5-Trinitro-1,3,5-Triazine. J. Microbiol. Biotechnol Vol. 22, no. 10, 1311–1323.•     Lalić В., Ćeranić P., Baškalo D. (2023) A radioactive waste repository in the borderarea between the Republic of Croatia and BiH: Human security perspective. Security Dialogues Vol. 14, 115–134.•     Мићин S., Малиновић B. (2023) Инжењерство експлозива и експлозивних материја. Бања Лука, Универзитет у Бањој Луци, Факултет безбједносних наука.•     Mine Action Review, Clearing the Mines 2024, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Mine Action Review, Clearing the Mines 2023, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Mine Action Review, Clearing the Mines 2022, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Mine Action Review, Clearing the Mines 2021, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Mine Action Review, Clearing the Mines 2020, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Mine Action Review, Clearing the Mines 2019, https://www.mineactionreview.org/ (приступљено 27.08.2025.)•     Nachon C.T. (2004) The environmental impacts of landmines https://www.researchgate.net/publication/292482972_The_environmental_impacts_of_landmines•     Saračević L., Mihalj A., Samek D., Gradaščević N., Zovko E. (2003) Osiromašeniji uranijum u BiH. V. simpozij HDZZ Stubičke Toplice 2, 302-309.•     Taylor S., Lever J. H., Fadden J., Perron N., Packer B. (2009) Outdoor weathering and dissolution of TNT and Tritonal. Chemosphere Vol. 77, 1338–1345.•     Tucker W. A., Murphy G. J., Arenberg E. D. (2002) Adsorption of RDX to Soil with Low Organic Carbon: Laboratory Results, Field Observations, Remedial Implication. Soil and Sediment Contamination: An International Journal, Vol. 11, 809–826.•     Ћеранић П., Башкало Д. (2019) Еколошка безбједност Босне и Херцеговине. Полиција, безбједност, грађани, 2/2019, 25–45.•     US EPA. (2014) Technical Fact Sheet – 2,4,6-Trinitrotoluene (TNT). https://www. epa.gov/sites/production/files/201403/documents/ffrrofactsheet_contaminant_tnt_january2014_final.pdf. 15. 6. 2024.•     UNHCR (1998) UNHCR to clear land mines in Bosnia and Herzegovina. https://www.unhcr.org/news/news-releases/unhcr-clear-land-mines-bosnia-and-herzegovina. (приступљено 01.08.2025).
Keywords: landmines; explosive ordnance; human security; threats; vulnerability